The Relationship Between Patient Satisfaction with Interest in Using Health Services in Pamekasan Pegantenan Health Center: Hubungan Antara Kepuasan Pasien dengan Minat Penggunaan Pelayanan Kesehatan di Puskesmas Pegantenan Pamekasan - Mudlikah, Siti; Indrawati, Iing Yuli; Handajani, Diani Octaviyanti (Universitas Muhammadiyah Sidoarjo, 2020)
Puskesmas is one of the public sector services that prioritizes of quality health services. Good service is the hope of every visiting patient so that later the patient has and interest to make a return visit if you want to do the examination. Customer satisfaction or disappointment of service will affect his behavior after that. Objective: Knowledge the relationship between patient satisfaction with the interest to re-utilize healthservices at Pamekasan Pegantenan Puskesmas. The method of this research use Analytic, research with cross sectional approach. The, population of the study was 136 people using accidental sampling obtained by the number of samples 101 people. The results of this research is from 101 respondent as many as 57 respondent (56,4%) said they were satisfaied with Puskesmas service and 85 respondent (84,2%) were interested to take advantage of health services at Pukesmas. The result of lambda test, it is found that p=0.0031 and α=0,05. So p<α, it means there is relationship. The conclusion of this reasearch istThere is relationship between patient satisfaction and interest in reusing health services provided by Pegantenan Pamekasan health center in May 2018